PENGARUH METODE GAME BASED LEARNING BERBANTUAN MEDIA CROSSWORD PUZZLE TERHADAP KEMAMPUAN MELAFALKAN DAN PENGUASAAN KOSA KATA BAHASA JAWA SISWA KELAS V SEKOLAH DASAR DI SURABAYA - Dyah P, Mahallisa; Mustaji; Nukmatus Syahria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the influence of game based learning methods assisted by crossword puzzles on the ability to pronounce words and mastery of Javanese vocabulary, especially in basic uploaded material. The method sed is quasi experimental. The research population included 87 students at elementary school in Surabaya. The research sample consisted of 56 students consisting of two groups, namely class VA as the control class and class VB as the experimental class, each with 28 students. Data on pronunciation ability and mastery of Javanese vocabulary were obtained through pretest and posttest. The ability to pronounce Javanese vocabulary is obtained from tests in the form of reading material that students must read correctly, while data on mastery of Javanese vocabulary is obtained through tests in the form of essay questions. Data analysis used the t-test for independent samples. Based on the research results, hypothesis testing shows a significance value of 0.00 <0.05, which means H0 is rejected. Therefore, it can be concluded that the game based learning method assisted by crossword puzzles affects the ability to pronounce words and mastery of Javanese vocabulary for class V students Elementary school in Surabaya.